TSO Games -- On the decidability of safety games under the total store order semantics - Spengler, Stephan; Sil, Sanchari (Electronic proceedings in theoretical computer science, 2023)
We consider an extension of the classical Total Store Order (TSO) semantics by expanding it to turn-based 2-player safety games. During her turn, a player can select any of the communicating processes and perform its next transition. We consider different formulations of the safety game problem depending on whether one player or both of them transfer messages from the process buffers to the shared memory. We give the complete decidability picture for all the possible alternatives.